Laparoscopic Extended Cholecystectomy for Early Gall Bladder Cancer - Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Journal of Nepal Health Research Council, 2021)
Background: Laparoscopic approach for early gall bladder cancer (T1b and T2) has been seen to have equal or better early outcomes and late outcomes in terms of overall survival rate and recurrence rate. Methods: This is a prospective cross sectional observational study performed including all consecutive patients who were diagnosed with gall bladder cancer by a single surgical team from August 2018 to February 2020 at Kathmandu Medical College Teaching Hospital or referred from outside for completion extended cholecystectomy where laparoscopic cholecystectomy was done in some other centre. Results: The mean age of the patients was 51.01±9.42 years in the laparoscopic extended cholecystectomy (N=10) group and 49.6±8.35 years in the open extended cholecystectomy (N=10) group (p value=0.711). Conversion rate was 20% in laparoscopic group. The operative time was longer in the laparoscopic group (287 +/-66.50 minutes, 120.0 to 446 minutes vs. 200+/-66.50 minutes, 100 to 405.0 minutes; p< 0.004.However, the laparoscopic extended cholecystectomy group showed faster time to oral intake and time to first passage of flatus and had shorter hospital stay by 2.2 days (4.8+/-0.78 days) than open approach 7+/-0.81 days.(p value=0.00).There were no significant differences between the groups in the tumour size (p=0.079) and number of harvested lymph nodes 9.3 (5 to 13) in laparoscopic group vs. 11.2 (8 to 15) in open extended cholecystectomy group (p=0.250). Conclusions: Laparoscopic extended cholecystectomy is feasible in early gall bladder cancer along with achievement of oncological safety. Keywords: Gall bladder cancer; laparoscopic extended cholecystectomy; open extended cholecystectomy